The effects of a structured educational program on preparedness for self-employed careers in Italian undergraduate nursing students: Gli effetti di un programma educativo strutturato sulla preparazione alle carriere autonome degli studenti universitari italiani di infermieristica - Rocco, Domenico; Caruso , Rosario; Magon , Arianna; Notarnicola, Ippolito; Stievano, Alessandro (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: In the Italian and also international contexts, there is a paucity of evidence testing whether a structured educational intervention delivered from remote might be useful in increasing the levels of preparedness for self-employed careers among third-year nursing students, despite freelance nursing careers are a promising component of the current labour market. This study aimed to test the effects of a structured educational program on the preparedness for self-employed careers in Italian undergraduate nursing students. Methods: The study was quasi-experimental and nonrandomized and employed a pre/post-intervention approach with convenience sampling. Data were collected before the structured education program was delivered (T0) and up to one day after the instruction was delivered (T1).Results: In this study, 717 third-year nursing students were enrolled. The most significant difference between T0 and T1 was in the domain of knowledge about pensions and retirement issues, followed by administrative rules knowledge. There were substantial variations between T0 and T1 in the area of logistic characteristics in determining the price of a freelance nursing activity, as well as scores in the domain of care complexity in determining the price of the independent nursing occupation.Conclusions: This study proved the short-term impacts of a structured educational program on enhancing levels of preparation for self-employed professions among Italian undergraduate nursing students. This topic requires more attention as the demands of prepared healthcare workers to undertake self-employed careers necessitate a greater capacity to properly educate nursing students for self-employed occupations within their undergraduate path.